Respiratory and other illnesses among the jute-mill workers in an industrial unit of Bangladesh - Rhaman, Mir Masudur; Morshed, M Abu Hana Golam; Sayeed, M Abu (IMC Journal of Medical Science, 2019)
Background and aims: Bangladesh produces 33% of the world’s jute and about 40 million people in Bangladesh are directly or indirectly involved in the jute sector. The jute (organic) dust inhalation causes byssinosis and other respiratory illnesses. However, no study has yet addressed the health status of the jute handlers/workers in Bangladesh. This study aimed to determine the prevalence of respiratory illnesses among the Jute Mill Workers (JMWs). Additionally, this study tried to find out the overall health status of the JMWs which included presence of non-communicable diseases (NCD) and its related risk, which are usually ignored. Study design: A cross-sectional study conducted in a purposively selected jute mill - 40km off from Dhaka City. Of the 5500 workers, a list of 600 workers was provided by the mill authority for enrollment in the study. The investigations included – a) interviewing on socio-demography and clinical history; b) anthropometry (height, weight, waist- and hip-circumference); c) blood pressure measurement; d) estimation of fasting blood glucose and lipids; e) peak flow meter test; f) spirometry; g) high resolution computerized tomography (HRCT) and electrocardiography. Results: Of the enlisted 600 jute mill workers, 514 (men / women = 478 / 36) took part in the study. The response rate was 85%. For overall estimate of bio-physical characteristics (n = 514), the means (95% confidence interval) of age, body mass index (BMI), waist-hip ratio (WHR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 44.19 (43.34 – 45.04) years, 24.44 (24.16 – 24.73), 0.90 (0.90 – 0.91), 118.9 (117.4 – 120.4), 79.69 (78.81 – 8/0.54), respectively. Regarding social class and education, 84.4% were from non-affluent (poor) class and 50% were illiterate. About 88% of the JMWs had been working for ≥42 hours a week and 91.6% were exposed to moderate or heavy work (equivalent to ≥60 min walk). The prevalence of breathlessness, tightness of chest and chronic cough were 16.5%, 25.7% and 16.3%, respectively. The restrictive and obstructive pulmonary functions were detected in 7.0% and 0.8% of study population respectively. The prevalence of systolic hypertension was 16.5%, diastolic hypertension was 7.2% and diabetes (IFG+DM) was 13.3%. They had increased cardiovascular risks – hypertriglyceridemia (23.9%) and hypercholesterolemia (24.3%). Conclusions: JMWs have been suffering mostly from respiratory illnesses and a substantial number of them suffer from undiagnosed hypertension, diabetes and other non-communicable diseases. Dyslipidemia was also prevalent as a potential risk factor. The study could not assess ocular, auditory, musculoskeletal and mental health and it suggests that a well designed study should address these health related problems of JMWs. IMC J Med Sci 2019; 13(1): 007